The relationship between eccentric hamstring strength and dynamic stability in elite academy footballers - Rhodes, D.; Jeffrey, J.; Maden-Wilkinson, J.; Reedy, A.; Morehead, E.; Kiely, J.; Birdsall, D.; Carling, C.; Alexander, J. (Science and Medicine in Football, 2020)
Objectives: Previous research describes dynamic stability and functional strength as key aetiological risk factors associated with lower limb non-contact musculoskeletal injury. Due to the multifactorial nature of injury risk, relationships between the two factors will inform injury management and training design.